Characterization of pressure retarded osmosis lab-scale systems. Issue 48 (20th October 2016) - Giacalone, F.; Cipollina, A.; Grisafi, F.; Tamburini, A.; Vella, G.; Micale, G.
Abstract: Power generation from salinity gradient is a viable alternative to produce energy from renewable sources. Pressure Retarded Osmosis (PRO) is one of the technologies proposed so far for the exploitation of such energy source. In the present preliminary work, two different geometry modules were tested under atmospheric pressure (i.e. forward osmosis or depressurized-PRO conditions). The first one is a conventional planar geometry cell. The second is a customized cylindrical membrane module, able to mechanically support the osmotic membrane along with the spacers. The latter, thanks to its design, allows membranes and spacers to be easily changed for testing purposes. A novel simplified procedure is proposed and employed in the planar geometry module to characterize an asymmetric membrane commercially available (i.e. assessing the water and salt permeability coefficients and the porous structure parameter). The parameters found were employed to mathematically estimate the permeate fluxes experimentally assessed and a very good agreement was found. Artificial solutions were employed for the experimental campaign: distilled water as feed solution and water–NaCl solution at different concentrations as drawing agent. Three different spacers were tested in the cylindrical geometry module thus highlighting the easy interchangeability of its components. Preliminary results confirmed that the spacer mesh open area is a critical issue affecting fluid dynamics (transport phenomena and pressure drop) along with membrane deformation.